2016
DOI: 10.1123/jtpe.2014-0095
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Health-Related Fitness Knowledge, Perceived Competence, Self-Determination, and Physical Activity Behaviors of High School Students

Abstract: The purpose of this study was (a) to test a hypothesized model of motivation within the context of conceptual physical education (CPE), and (b) to explore the strength and directionality of perceived competence for physical activity as a possible mediator for health-related fitness knowledge (HRFK) and physical activity behaviors. High school students (N = 280) at the end of a CPE course completed the following: Behavioral Regulation in Exercise Questionnaire–2, Godin Leisure–Time Exercise Questionnaire, Perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 3 publications
2
15
1
Order By: Relevance
“…We have run the appropriate correlational analysis and have found no significant correlations between any types of motivation and HRFK. This is in line with research from Sun and Chen [55], who found no relationship between motivation and knowledge learning, and at odds with research that has found a relationship between cognitive knowledge and autonomous motivation [56], and between HRFK and controlled motivation [104]. Sun and Chen [55] explain the lack of connection between motivation and knowledge learning in traditional PE in terms of it being centered on "happy, busy, good", which might be motivating, but not lead to learning achievement.…”
Section: Health-related Fitness Knowledgesupporting
confidence: 90%
See 1 more Smart Citation
“…We have run the appropriate correlational analysis and have found no significant correlations between any types of motivation and HRFK. This is in line with research from Sun and Chen [55], who found no relationship between motivation and knowledge learning, and at odds with research that has found a relationship between cognitive knowledge and autonomous motivation [56], and between HRFK and controlled motivation [104]. Sun and Chen [55] explain the lack of connection between motivation and knowledge learning in traditional PE in terms of it being centered on "happy, busy, good", which might be motivating, but not lead to learning achievement.…”
Section: Health-related Fitness Knowledgesupporting
confidence: 90%
“…If this were the case, it would be beneficial to increase HRFK in order to achieve the goal of life-long participation in PA [1], and achieve some of the documented health benefits following PA [7]. However, findings in previous studies are not in agreement about the relationship between HRFK and PA, with some finding a positive relationship [105], and others finding no significant relationship [104]. It, therefore, seems unclear what the practical implications of increasing HRFK are [106].…”
Section: Health-related Fitness Knowledgementioning
confidence: 99%
“…The BREQ-2 has been validated among a variety of populations. 12,38,39 For example, Haslem et al. 12 found that the instrument demonstrated acceptable construct validity (CFI = .93, SRMR = .07, and RMSEA = .07) and scale reliability ( α s = .77–.90) among 280 high school physical education students.…”
Section: Methodsmentioning
confidence: 99%
“…12,38,39 For example, Haslem et al. 12 found that the instrument demonstrated acceptable construct validity (CFI = .93, SRMR = .07, and RMSEA = .07) and scale reliability ( α s = .77–.90) among 280 high school physical education students. Due to our small sample size, we were not able to examine construct validity of the scales, but their reliability values were all acceptable ( α s = .73–.86).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation